ENTREPRENEURIAL MARKETING START-UP MEDIA SIBER LOKAL KEMPALAN.COM DI JAWA TIMUR: STRATEGI MENUJU SUSTAINABILITY? - Freddy Mutiara (Jurnal Manajemen Pemasaran, 2022)
Entrepreneurial marketing is marketing practices for small companies and start-ups that grow through entrepreneurial activities in the midst of limited company resources and the uncertainty of business environment. In research using qualitative research methods through descriptive case studies, it was found that entrepreneurial marketing plays an important role in the operational success of cyber media start-up company Kempalan.com. Intuitively, agilely, and innovatively according to the dynamics of business environment faced by cyber media Kempalan.com, entrepreneurial marketing plays a role in building the company's competitiveness in the industry. In addition to carrying out entrepreneurial marketing, Kempalan.com needs to scale-up and achieve business economies of scale for the company's sustainability in the future. Abstrak: Entrepreneurial marketing merupakan praktik pemasaran perusahaan kecil dan start-up yang bertumbuh melalui aktivitas kewirausahaan di tengah keterbatasan sumber daya perusahaan dan ketidakpastian lingkungan bisnis. Dalam penelitian menggunakan metode penelitian kualitatif melalui studi kasus deskriptif ditemukan bahwa entrepreneurial marketing berperan penting dalam keberhasilan operasional perusahaan start-up media siber Kempalan.com. Secara intuitif, agile, dan inovatif sesuai dinamika lingkungan bisnis yang dihadapi media siber Kempalan.com, entrepreneurial marketing berperan membangun daya saing perusahaan di dalam industri. Selain menjalankan entrepreneurial marketing, Kempalan.com perlu melakukan scale-up dan mencapai skala ekonomi bisnisnya untuk keberlanjutan perusahaan di masa depan.